Chaperone properties of Escherichia coli thioredoxin and thioredoxin reductase. - Kern, Renée (2003)
Thioredoxin, thioredoxin reductase and NADPH form the thioredoxin system and are the major cellular protein disulphide reductase. We report here that Escherichia coli thioredoxin and thioredoxin reductase interact with unfolded and denatured proteins, in a manner similar to that of molecular chaperones that are involved in protein folding and protein renaturation after stress. Thioredoxin and/or thioredoxin reductase promote the functional folding of citrate synthase and alpha-glucosidase after urea denaturation. They also promote the functional folding of the bacterial galactose receptor, a protein without any cysteines. Furthermore, redox cycling of thioredoxin/thioredoxin reductase in the presence of NADPH and cystine stimulates the renaturation of the galactose receptor, suggesting that the thioredoxin system functions like a redox-powered chaperone machine. Thioredoxin reductase prevents the aggregation of citrate synthase under heat-shock conditions. It forms complexes that are more stable than those formed by thioredoxin with several unfolded proteins such as reduced carboxymethyl alpha-lactalbumin and unfolded bovine pancreatic trypsin inhibitor. These results suggest that the thioredoxin system, in addition to its protein disulphide isomerase activity possesses chaperone-like properties, and that its thioredoxin reductase component plays a major role in this function.